Energy-Efficient Optimization Design for the Multi-Color LED Based Visible Light Communication Systems under Illumination Constraints - Yu Zuo (Applied Sciences, 2018)
Visible light communications (VLCs) utilizing multi-color light-emitting diodes (LEDs) can achieve a high modulation bandwidth and high-quality illumination compared with phosphor-converted LEDs, which have attracted much attention. However, the spectrum overlapping of different colors may cause the crosstalk problem, which should be considered in the practical multi-color LED-based VLC systems. Due to the ever-increasing energy consumption, the interest in an energy-saving communication technique has further increased. In this paper, in order to maximize energy efficiency, an optimization problem of the optical power allocation scheme is formulated for the multi-color LED-based VLC systems under the necessary communication requirements and illumination constraints with luminance, chromaticity, and signal to interference plus noise ratio (SINR) constraints. Simulation results indicate that the proposed optimal power allocation scheme can reduce energy consumption while satisfying the illumination and communication requirements.